Gender member-gender mender: charlotte ramsay lennox and her fictions - Melchiorre,Sonia Maria (2015)
Charlotte Ramsay Lennox is one of the many women novelists long forgotten by scholars that only very recently has received the critical attention she deserves. This paper aims at the reconsideration, and the inclusion in the tradition, of one of the greatest talents of the British literary scene of the eighteenth century. Charlotte Ramsay Lennox must, by now, be recognized as one of the most versatile writers of her generation: she wrote poetry, fiction, criticism - she was the first woman to write on Shakespeare and his sources in the eighteenth century, with her Shakespeare Illustrated (1753), and was the editor of one of the first magazines which serialised novels.